Incorporation of recycled aggregates from construction and demolition waste in paver blocks - Pederneiras,Cinthia Maia (2020)
ABSTRACT: The consumption of natural resources and energy increased proportionally with the growth of the world population and its economic level. There was an increasing exponential consumption of natural resources, which implied an increase in environmental impacts. The construction sector is responsible for a very significant production of construction and demolition waste (CDW). Thus, there is a concern in search of a more sustainable final disposal. Many studies have been investigated the development of new materials with the incorporation of recycled aggregates from CDW. This paper presents a study of performance evaluation of concrete blocks produced with CDW. For that purpose, an experimental campaign was performed, including a characterization of the aggregates used. The incorporation of 100% of fine and coarse recycled aggregates. The mixtures were designed according to the condition of the aggregate (dry, washed or saturated). The performance of these blocks was evaluated in terms of mechanical strength and water absorption. Some additional tests were also performed to deeper analyze of the microstructure of these blocks. To assess the durability of the concrete blocks, a full-scale road was built. The results were very positive, since there were no significant differences between the modified concrete blocks and the reference sample (0% of the CDW). The modified block with fine aggregate presented the best performance of all the blocks, concerning mechanical strength. In addition, the performance of concrete blocks with washed recycled aggregates had a better performance compared to the others. The results obtained were satisfactory for the application of the blocks in the streets with low movement and low load.